5 --> 2 is subtract 3
2 --> -1 is subtract 3
-1 --> -4 is subtract 3
Let's apply this rule until all blanks are filled.
5, 2, -1, -4, ___, ___, ___,...
We have three blanks, so let's continue from -4 three times.
-4 -(3) = -7
5, 2, -1, -4, -7, ___, ___,...
We have one blank filled.
-7 -(3) = -10
5, 2, -1, -4, -7, -10, ___,...
We have two blanks filled.
-10 -(3) = -13
5, 2, -1, -4, -7, -10, -13,...
We have all three blanks filled- let's see our answers.
We have:
-7
-10
-13
These are your three answers.
I hope this helps!